A new risk-scoring system to predict Xp11.2 translocation renal cell carcinoma in adults. Issue 3 (March 2021) - Shi, Qiancheng; Liu, Ning; Zhu, Yiqi; Qu, Feng; Xu, Linfeng; Li, Xiaogong; Zhang, Gutian; Guo, Hongqian; Li, Dongmei; Gan, Weidong
Objective: The objective was to derive and validate a practical scoring system for preoperative diagnosis of Xp11.2 translocation renal cell carcinoma (RCC) in adults. Methods: Epidemiology, symptomatology, and imaging methods were correlated between patients with common RCC and those with Xp11.2 translocation RCC using a derivation study (N = 6352) and a validation study (N = 127). Univariate analysis of risk factors was performed to derive a scoring system to predict the occurrence of Xp11.2 translocation RCC in adults. The Hosmer–Lemeshow goodness-of-fit test and receiver operating characteristic (ROC) curve were used to validate the scoring system. Results: Based on odd ratios, three low-risk factors (sex, gross haematuria, and intratumoural calcification) and three high-risk factors (age, unenhanced computed tomography density, and enhancement pattern) were given weighted scores of 1 and 2, respectively. Patients who scored 3 to 5 points underwent an additional magnetic resonance imaging examination. The final scoring system had a sensitivity of 81.0% and a specificity of 98.0%. Conclusion: We established a practical scoring system for the preoperative diagnosis of Xp11.2 translocation RCC in adults, which can be optimised through further clinical findings in the future.